Compensation and Damages for Medical Malpracticeand Civil Liability of Medical Entities in Poland - Walczak , Damian; Krupa, Dorota; Musiałkiewicz, Robert (Studia Oeconomica Posnaniensia, 2015)
The purpose of this article is to identify the economic and legal aspects of compensation for medical errors. Issues related to the civil liability of medical entities and their economic consequences for participants in the health care system will be addressed in the paper. Both the common phrase ’primum non nocere and a fragment of the medical oath contained in the Code of Medical Ethics ’to the best of my knowledge prevent suffering and prevent disease, and to help patients without any difference’ refer to making the best efforts on the part of doctors and the medical world to exercise their profession fairly. Unfortunately, in practice, medical errors do occur and have serious consequences. On the one hand, those consequences result in health effects suffered by the patient who may require a long-term treatment or rehabilitation as part of his/her recovery due to medical arror, but it may also be the case that the patient may well never recover or may even lose his/her life. On the other hand such errors relate to doctors and medical personnel who have committed a specifi c error as well as to the entities on the premises in which the event took place. Th erefore the sphere of the scope and type of liability are essential. Th e latter is inextricably linked to the insurance benefits’ market and to the problem of fi nancing a health care system.